Actinobacillus pleuropneumoniae induces SJPL cell cycle arrest in G2/M-phase and inhibits porcine reproductive and respiratory syndrome virus replication. Issue 1 (December 2015) - Ferreira Barbosa, Jérémy; Labrie, Josée; Beaudry, Francis; Gagnon, Carl; Jacques, Mario
Abstract Background Porcine reproductive and respiratory syndrome virus (PRRSV) is one of the most important pathogens in the swine industry and causes important economic losses. No effective antiviral drugs against it are commercially available. We recently reported that the culture supernatant ofActinobacillus pleuropneumoniae, the porcine pleuropneumonia causative agent, has an antiviral activityin vitro against PRRSV in SJPL cells. Objectives of this study were (i) to identify the mechanism behind the antiviral activity displayed byA. pleuropneumoniae and (ii) to characterize the active molecules present in the bacterial culture supernatant. Methods Antibody microarray analysis was used in order to point out cellular pathways modulated by theA. pleuropneumoniae supernatant. Subsequent, flow cytometry analysis and cell cycle inhibitors were used to confirm antibody microarray data and to link them to the antiviral activity of theA. pleuropneumoniae supernatant. Finally, A. pleuropneumoniae supernatant characterization was partially achieved using mass spectrometry. Results Using antibody microarray, we observed modulations in G2/M-phase cell cycle regulation pathway when SJPL cells were treated withA. pleuropneumoniae culture supernatant. These modulations were confirmed by a cell cycle arrest at the G2/M-phase when cells were treated with theA. pleuropneumoniae culture supernatant. Furthermore, two G2/M-phase cell cycle inhibitors demonstrated the ability to inhibit PRRSV infection, indicating a potential key role for PRRSV infection. Finally, mass spectrometry lead to identify two molecules (m/z 515.2 and m/z 663.6) present only in the culture supernatant. Conclusions We demonstrated for the first time thatA. pleuropneumoniae is able to disrupt SJPL cell cycle resulting in inhibitory activity against PRRSV. Furthermore, two putative molecules were identified from the culture supernatant. This study highlighted the cell cycle importance for PRRSV and will allow the development of new prophylactic or therapeutic approaches against PRRSV.